2012
DOI: 10.2144/000113873
|View full text |Cite
|
Sign up to set email alerts
|

Common Benzothiazole and Benzoxazole Fluorescent DNA Intercalators for Studying Alzheimer Aβ 1-42 and Prion Amyloid Peptides

Abstract: Amyloids are fibrillar protein aggregates associated with a number of neurodegenerative pathologies including Alzheimer and Creutzfeldt-Jakob disease. The study of amyloids is usually based on fluorescence with the dye thioflavin-T. Although a number of amyloid binding compounds have been synthesized, many are nonfluorescent or not readily available for research use. Here we report on a class of commercial benzothiazole/benzoxazole containing fluorescent DNA intercalators from Invitrogen that possess the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…In an interesting development, Stefansson and colleagues [239] noted that (i) the thiazole moiety is critical to binding [201], and (ii) that a number of modern, sensitive DNA-intercalating dyes also contain the thiazole nucleus. They showed [239] that these dyes too would bind to β-amyloid fibrils, albeit not normally (but cf. [240]) with quite with the same fluorescence enhancement as shown by…”
Section: Thioflavin S Thioflavin T and Derivativesmentioning
confidence: 99%
“…In an interesting development, Stefansson and colleagues [239] noted that (i) the thiazole moiety is critical to binding [201], and (ii) that a number of modern, sensitive DNA-intercalating dyes also contain the thiazole nucleus. They showed [239] that these dyes too would bind to β-amyloid fibrils, albeit not normally (but cf. [240]) with quite with the same fluorescence enhancement as shown by…”
Section: Thioflavin S Thioflavin T and Derivativesmentioning
confidence: 99%
“…Recently, Stefansson et al . reported that the fluorescent intensity of benzothiazole and benzoxazole dimers could increase several folds when the dyes were incubated with Hamster prion proteins [119]. Bresjanac et al .…”
Section: Other Proteinsmentioning
confidence: 99%
“…22,23 Consequently, various planar molecules/compounds/drugs which are known to interact and modulate DNA structure have been tested for their anti-amyloidogenic potential. [24][25][26] The best known drugs of this class included two FDA approved DNA intercalators, 4 0 -iodo-4 0 -deoxydoxorubicin for systemic amyloidosis 27,28 and mitoxantrone/picoxantrone against Ab brillation. 29,30 Traditionally, these compounds comprise simple class of planar organic molecules capable of modulating genetic and epigenetic expression via stacking in between adjacent base pairs of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…However, inhibition by EGCG by virtue of its hydrophobic/H-bond interactions requires thorough investigation behind its mechanism of action. To comprehensively understand the role of hetero-aromatic associations to interfere with the amyloidogenic pathways, we designed this current study by employing the pre-brillar structural coordinates of IAP amyloid-core containing sequence (NFGAILS), IAP (22)(23)(24)(25)(26)(27)(28) as our model system (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation